A text-centred rhetorical analysis of 1 Thessalonians 2:1–12 - Prinsloo, H.J. (Stellenbosch Theological Journal, 2023)
This article analyses 1 Thessalonians 2:1–12 from a rhetorical perspective. Instead of the typical approach used to analyse the letter in terms of ancient rhetorical theory, this article explains Paul’s rhetorical strategy found in the text itself; it is therefore called a text-centred rhetorical analysis which follows a minimum theoretical approach. Accordingly, the overall rhetorical strategy is identified in this pericope. A discussion of the dominant and supportive arguments and rhetorical techniques follows the identification. This article illustrates how Paul adapts the ancient letter style to achieve his rhetorical objectives. It remains critical to note Paul’s already favourable relationship with the congregants. Therefore, his authority does not need to be confirmed. In light of the accusations of the outsiders, he nevertheless finds it necessary to reaffirm his integrity or ethos.